Gender and attitudes toward welfare state reform: Are women really social investment promoters?. (July 2021) - Garritzmann, Julian L.; Schwander, Hanna
This article contributes to the study of the demand side of welfare politics by investigating gender differences in social investment preferences systematically. Building on the different functions of social investment policies in creating, preserving, or mobilizing skills, we argue that women do not support social investment policies generally more strongly than men. Rather, women demand, in particular, policies to preserve their skills during career interruptions and help to mobilize their skills on the labour market. In a second analytical step, we examine women's policy priorities if skill preservation and mobilization come at the expense of social compensation. We test our arguments for eight Western European countries with data from the INVEDUC survey. The confirmation of our arguments challenges a core assumption of the literatures on the social investment turn and women's political realignment. We discuss the implication of our findings in the conclusion.